2018
DOI: 10.1097/hjh.0000000000001740
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass independently associates with masked hypertension in young healthy adults

Abstract: This study highlights the importance of the early detection of masked hypertension as young apparently healthy adults already show an increased left ventricular mass index, thereby indicating increased risk for future cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Our findings from this rural population align with data from periurban settings in South Africa and SSA, where a high hypertension burden led to widespread LVH (40%) and diastolic dysfunction (25%), even in young patients with masked hypertension. 4,7,22 Notably, diastolic dysfunction in our rural sample is greater than contemporary reports from high-income countries in Europe (10%-25%). 23 Some variability is expected because diastolic parameters vary across studies based on an evolving expert consensus.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our findings from this rural population align with data from periurban settings in South Africa and SSA, where a high hypertension burden led to widespread LVH (40%) and diastolic dysfunction (25%), even in young patients with masked hypertension. 4,7,22 Notably, diastolic dysfunction in our rural sample is greater than contemporary reports from high-income countries in Europe (10%-25%). 23 Some variability is expected because diastolic parameters vary across studies based on an evolving expert consensus.…”
Section: Discussioncontrasting
confidence: 58%
“…Such contemporary data are needed for health systems to identify high-risk patient groups to prioritize and target with aggressive monitoring and treatment. 7 To address this unmet need, in 2014, we began collecting epidemiological data on a cohort of >5000 individuals from the Health and Socio-Demographic Surveillance System established in the Agincourt subdistrict, in rural South Africa, 8 where we documented a high burden of hypertension and obesity. 6 However, the severity of this CVD burden-as evidenced by end-organ damage-has not been measured in this region.…”
mentioning
confidence: 99%
“… 28 Furthermore, despite their young age those with masked hypertension had a greater adjusted odds ratio (1.67, 95% confidence interval 1.05–2.71, P = 0.031) for increased left ventricular mass index. 29 …”
Section: Resultsmentioning
confidence: 99%
“…The present study identified MH in 32.1% and 55% of PLHIV with OBP normotension or high-normal BP, respectively. The identification of MH is very important, since patients with MH frequently develop target organ damage prior to transitioning to sustained hypertension and MH confers a cardiovascular risk similar to that of sustained hypertension [27][28][29]. Data on the frequency of MH among PLHIV are scarce and primarily from countries outside SSA (e.g.…”
Section: Discussionmentioning
confidence: 99%